Catalytic cracking of petroleum vacuum residue in supercritical water media: Impact of α-Fe2O3 in the form of free nanoparticles and silica-supported granules. (1st November 2015) - Hosseinpour, Morteza; Fatemi, Shohreh; Ahmadi, Seyed Javad
Graphical abstract: Highlights: Catalytic and non-catalytic cracking reactions were studied in SCW, comparatively. Asphaltene conversions in SCW, maltene and coke formation were analyzed. Catalytic cracking showed lower coke formation rather than non-catalytic reaction. No phase transformation was occurred in supported catalyst after cracking reaction. Abstract: Catalytic cracking of bottom product from the vacuum distillation unit, i.e., vacuum residue (VR) was investigated in supercritical water (SCW) over different forms of iron oxide nano-catalyst as free α-Fe2 O3 nanoparticles and SiO2 -supported α-Fe2 O3 crystals. The effects of operational parameters including reaction temperature, reaction time, catalyst to oil weight ratio, and water to oil weight ratio were studied on the yield of maltene and coke produced from VR cracking as well as asphaltene conversion, in a batch autoclave reactor. SEM, XRD and TGA analyses were used to characterize the catalyst before and after the reaction. TGA and XRD images confirmed phase transformation of α-Fe2 O3 to magnetite (Fe3 O4 ) during reaction with free nanoparticles, and SEM images showed agglomeration of the nanoparticles significantly. It was resulted that silica-supported α-Fe2 O3 catalyst was more stable and more effective than that of free nanoparticles in the process of VR cracking. The suggested mechanism of the reaction would be a cycle beginning with oxidative cracking of hydrocarbons by the lattice oxygen provided from reduction of α-Fe2 O3 to Fe3 O4 then releasing the active hydrogen by SCW gas shift reaction to hydrocracking VR and production of aliphatic compounds. At the same time, the reduced form of the catalyst (Fe3 O4 ) would be converted to α-Fe2 O3 by the oxygen atom released from SCW.